An Analysis of Influencing Factors of Entrepreneurial Intentions and Behavior of Undergraduate Students at a University in Guangxi, China - Wu, Jun (Scholar: Human Sciences, 2025)
Purpose: This research aims to examine the factors that influence undergraduate students' entrepreneurial intentions and behavior at Guangxi University of Science and Technology. The framework contains variables, which are creativity, entrepreneurial education, personal attitude, subjective norms, perceived behavioral control, entrepreneurial intentions, and entrepreneurial behavior. Research Design, Data, and Methodology: A quantitative research approach was employed in this study, involving a sample size of 500 undergraduate students from Guangxi University of Science and Technology. Non-probability sampling methods include judgmental, quota and convenience sampling. Before the data collection, the index of item-objective congruence (IOC) and pilot test (n=50) with Cronbach’s Alpha are employed. The data was analyzed using structural equation modeling (SEM) and confirmatory factor analysis (CFA) to assess model fit, reliability, and construct validity. Results: The findings reveal that creativity, entrepreneurial education, personal attitude, subjective norms, and perceived behavioral control significantly impact both entrepreneurial intentions and entrepreneurial behavior. Among these factors, perceived behavioral control has the strongest influence. Conclusions: This study recommends that university administrators evaluate the factors that influence student entrepreneurship and assess the developmental levels in this area. The findings of this research provide valuable insights for organizers and administrators of entrepreneurial activities in higher education, enabling them to promote student entrepreneurship and create more employment opportunities.